tRNA hopping: enhancement by an expanded anticodon. - O'Connor, M (1989)
At a low level wild-type tRNA(1Val) inserts a single amino acid (valine) for the five nucleotide sequence GUGUA which has overlapping valine codons. Mutants of tRNA(1Val) with an insertion of A or U between positions 34 and 35 of their anticodons have enhanced reading of the quintuplet sequences. We propose that this decoding occurs by a hopping mechanism rather than by quintuplet pairing. Such hopping involves disengagement of the paired codon and anticodon with the mRNA slipping two (or more) bases along the ribosomal--peptidyl tRNA complex and subsequently re-pairing at a second codon--the landing site. The mutant with the anticodon sequence 3'CAAU5' 'hops' over the stop codon in the mRNA sequence GUG UAA GUU with the insertion of a single amino acid (valine). In contrast, in reading the same sequence, the mutant with the anticodon 3'CAUU5' hops onto the stop with the insertion of two valine residues. It is likely that in some instances of hopping alternate anticodon bases are used for the initial pairing and at the landing site.